2020
DOI: 10.1038/s41563-020-0688-6
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between thermodynamics and kinetics in the solid-state synthesis of layered oxides

Abstract: In the synthesis of inorganic materials, reactions often yield non-equilibrium kinetic byproducts instead of the thermodynamic equilibrium phase. Understanding the competition between thermodynamics and kinetics is fundamental towards the rational synthesis of target materials. Here, we use in situ synchrotron X-ray diffraction to investigate the multistage crystallization pathways of the important two-layer (P2) sodium oxides Na 0.67 MO 2 (M = Co, Mn). We observe a series of fast non-equilibrium phase transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
198
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(211 citation statements)
references
References 58 publications
13
198
0
Order By: Relevance
“…In these structures, “P” or “O” indicates prismatic or octahedral coordination, respectively, for Na + , and “2” or “3” represents the number of TM layers with different types of oxygen stacking in a single unit cell [61,67] . Because of the large ionic radius of the Na + ion, both octahedral and prismatic coordination is possible; thus, the most common structures are P2, P3, O2, and O3 in layered sodium TMOs [28] …”
Section: Fundamental Science and Theories Of Anionic Redox In Cathodementioning
confidence: 99%
“…In these structures, “P” or “O” indicates prismatic or octahedral coordination, respectively, for Na + , and “2” or “3” represents the number of TM layers with different types of oxygen stacking in a single unit cell [61,67] . Because of the large ionic radius of the Na + ion, both octahedral and prismatic coordination is possible; thus, the most common structures are P2, P3, O2, and O3 in layered sodium TMOs [28] …”
Section: Fundamental Science and Theories Of Anionic Redox In Cathodementioning
confidence: 99%
“…7. 16 Similar to P2 and O3-type phases, doping may also help to improve the performance of P3-type layered oxides. For example, Wang et al found that substitution of a small quantity of oxygen for uorine to form Na 0.65 Mn 0.75 -Ni 0.25 F 0.1 O 1.9 could suppress the P3-O1 transition.…”
Section: O3-typementioning
confidence: 99%
“…The reaction selectivity of K 3 BiQ 3 (Q = S, Se) directly proceeding the formation of the KBiQ 2 ternary is postulated to be structural in origin as opposed to energetic. In-situ studies observing the phase formation found the composition of the first transient phase to be that which yielded the largest energy release 81 or the fastest energy release 30 . The former does not apply for these chalcogenide systems as the formation of K 3 BiQ 3 is less energetically favorable than the β- In order to isolate α-KBiSe 2 , the product was quenched at 650°C and annealed.…”
Section: Methodsmentioning
confidence: 99%